ТӘУЕЛСІЗДІК ЖЫЛДАРЫНДАҒЫ ҚАЗАҚСТАННЫҢ КӨЛІК КЕШЕНІНІҢ ДАМУЫ БАҒЫТТАРЫ МЕН ПЕРСПЕКТИВАЛАРЫ. - Нұрғалиева, Г. Қ. (Journal of Economic Research & Business Administration, 2015)
Одним из уроков кризиса стало изменение представления о роли государства в рыночной экономике.Сегодня мир признал, что государство и рынок должны сосуществовать, и государство может осуществлять надзор, например, в финансовом секторе и в сфере контроля за качеством строительства дорог, внедрения инновационных технологий, гармонизации казахстанских стандартов с международными стандартами управления транспортом. To one of crisis lessons became representation change about a state role in market economy. Today the world recognised that the state and the market should co-exist, and the state can carry out supervision, for example, in financial sector and in sphere of the control over quality of a construction of roads, introduction of innovative technologies, harmonisation of the Kazakhstan standards with the international standards of management of transport.